Evaluating the Effectiveness and Complications of Robotic vs Other Surgery Techniques for Mitral Valve Repair or Replacement: A Comprehensive Systematic Review and Meta-analysis - Carlos Esteban Vidal Valderrama; Ramon Isaac Zavala Garcia; Yeisson Rivero Moreno; Raul Antunez Perez; Jessica Edith Acevedo Rodriguez; Vanessa Pamela Salolin-Vargas; Leopoldo David Trujillo-García; Mauricio Alejandro Saldaña-Ruiz; Noe Alejandro Zúñiga González; Vanessa Jarelly Rodríguez-Huerta; Carolina Cantú Navarro (International Journal of Medical Students, 2024)
BACKGROUND: Mitral valve repair and replacement are common critical surgical procedures. Traditional open-heart surgery has long been the standard approach, offering reliable outcomes through direct visualization and access to the heart. However, advancements in minimally invasive techniques, particularly robotic-assisted surgery, have introduced new possibilities in the field of cardiac surgery and benefits to the patients regarding the outcomes and complications. Despite these advantages, the technique requires specialized training and has a steep learning curve, leading to variability in outcomes depending on the surgeon’s experience. This abstract aims to compare robotic mitral valve repair versus other surgical techniques, providing insights into the evolving approaches to performing this procedure.